POLICY MODEL FOR THE USE OF ELECTRONIC DOCUMENTS AS A PROOF TOOL IN CRIMINALACTION AFTER THE APPLICATION OF LAW NO 19 OF 2016 - Muhammad Afied Hambali (UNTAG Law Review, 2019)
This paper aims to analyze the policy model of the use of electronic documents as evidence in criminal acts based on Law No. 19 of 2016. The development of information technology has significantly transformed the conventional socialization system into a digital system. This affects the emergence of new legal actions in a community. The form of the new legal action needs to be adjusted and harmonized with existing legislation, such as the use of electronic documents as evidence that will be used as a means of verification in court. Based on the analysis it was revealed that Law No. 19 of 2016 as a legal umbrella for regulating criminal acts in cyberspace is still experiencing many obstacles, therefore it must be harmonized with the relevant criminal law because if it is different then it will cause legal imbalance so that it will increasingly make it difficult for law enforcers to enforce the law.